InvestKL says more MNCs coming - The Sun, Eva Yeong (2012)
KUALA LUMPUR: InvestKL Malaysia is confident of attracting more multinationals to invest in Greater Kuala Lumpur and the Klang Valley despite the competitive and challenging global economy due to encouraging investor sentiment, said its CEO Zainal Amanshah.